The Association of Deep versus Minimal Neuromuscular Blockade with Surgical Conditions and Postoperative Pulmonary Complications: A Systematic Review - Febrina Sintari Caniago; Rudy Kurniawan Putra (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: The optimal depth of neuromuscular blockade (NMB) for surgical procedures remains a subject of significant clinical debate. Deep NMB (DNMB) is hypothesized to improve intraoperative surgical conditions, particularly in minimally invasive surgery. However, its association with critical patient-centered outcomes, such as postoperative pulmonary complications (PPCs), is uncertain, creating a gap between surgeon-centric benefits and patient-safety metrics. METHODS: A systematic review was conducted in adherence with PRISMA guidelines. We performed a systematic search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library for randomized controlled trials (RCTs) in adult patients undergoing surgery. Studies comparing deep NMB (defined as Train-of-Four count 0, post-tetanic count ≥ 1) to moderate or minimal NMB (TOF count ≥ 1) were included. Primary outcomes were categorized into: (1) surgical conditions (surgical rating scales, intraoperative movement) and (2) postoperative pulmonary complications (PPCs). Secondary outcomes included postoperative pain, recovery metrics, and resource utilization. Pooled data were analyzed using a random-effects model. RESULTS: A total of 20 RCTs, comprising 2,388 patients, were included. Deep NMB was associated with statistically significant improvements in surgical conditions, including a higher surgical condition score (Mean Difference: 0.52, 95% Confidence Interval [CI]: [0.37, 0.67]) and an increased rate of acceptable surgical conditions (Relative Risk: 1.19, 95% CI: [1.11, 1.27]). Furthermore, DNMB was associated with a significant reduction in the rate of intraoperative patient movement (RR: 0.19, 95% CI: [0.10, 0.33]). In contrast, there was no sufficient evidence that DNMB was associated with a reduction in the incidence of composite PPCs or serious adverse events (SAEs) (Peto Odds Ratio: 0.90, 95% CI: [0.56, 1.42]). DNMB was associated with a significant reduction in immediate postoperative pain in the PACU and at 24 hours, but not at 48 hours. No significant differences were found for duration of surgery or total length of hospital stay. DISCUSSION: The findings reveal a clear divergence between surgeon-centric and patient-centric outcomes. The benefits of DNMB are primarily related to optimization of the surgical field. The lack of an independent association with PPCs suggests that pulmonary outcomes are not dictated by intraoperative NMB depth, but rather by the avoidance of postoperative residual neuromuscular blockade (RNMB). The observed PPC benefit in some literature is likely a confounding artifact of the required use of sugammadex for reversal of DNMB, which is independently associated with a lower risk of RNMB and PPCs compared to neostigmine. CONCLUSION: Deep NMB is a significantly effective strategy for improving surgical conditions and reducing intraoperative patient movement, which may also provide a transient postoperative pain benefit. However, it should not be employed with the primary expectation of reducing postoperative pulmonary complications. The prevention of PPCs is more directly related to complete neuromuscular reversal, verified by quantitative monitoring, rather than the intraoperative depth of blockade.